Improving Prospective Physics Teachers’ Conceptual Understanding of Moon Phases Through an Integrated Observational and Virtual Simulation Learning - Theo Jhoni Hartanto; Maya Mustika; Gunarjo Suryanto Budi (Universitas Pendidikan Mandalika, 2025)
Although the moon's phases are directly observable phenomena, students at all levels of education consistently have misconceptions about their causes. This indicates a cognitive gap between observational experience and the scientific models that are supposed to explain it. This study aims to improve prospective physics teachers’ conceptual understanding of moon phases through an integrated observational and virtual simulation learning. Employing a pre-experimental method with a one-group pretest-posttest design, the study involved a total sample of 19 students from the Department of Physics Education. The research instrument was a conceptual understanding test adapted from the Moon Phases Concept Inventory (MPCI), consisting of 11 items and accompanied by a Certainty of Response Index (CRI). The results revealed a substantial increase in students’ understanding, as indicated by the mean pretest score of 2.68 (SD = 1.108; SE = 0.254) and the mean posttest score of 9.47 (SD = 1.744; SE = 0.400). The Shapiro-Wilk normality test showed that the pretest data were normally distributed (Sig. = 0.130), while the posttest data were not (Sig. = 0.001). Consequently, the Wilcoxon signed-rank test was used and confirmed a statistically significant difference between the pretest and posttest scores (Asymp. Sig. 2-tailed = 0.000). These findings indicate that combining direct observation and virtual simulation contributes meaningfully to the improvement of prospective physics students’ conceptual understanding of Moon phases. These findings also illustrate the value of integrating real-world experiences and simulation technology into the physics teacher education curriculum to strengthen conceptual competencies, spatial skills, and pedagogical readiness while supporting deep learning.